A Study on Mental Efficiency of Rural Older Women - Dr.K.Maheswari, Mrs.A.Sivapriya (International Journal of Scientific Research and Management (IJSRM), 2017)
Old age is a precious period of every one’s life because they have an opportunity to reflect their life experiences. Freud has also mentioned that the behavior of the person is influenced by the childhood experiences. Old age is a stage, when people move away from previous to more desirable period to less desirable period. The social attitudes toward the elderly are more important because it reflects the social treatment of the senior citizens and it is every old person’s responsibility to improve the self concept. The declination of mental ability of older persons depends on individual differences and environment. The present research study has focused on the female elderly with regard to their mental efficiency. The aim and objectives of the study is to identify the socio demographic profile of the older persons and to analyze the mental efficiency and to suggest the suitable measures to enhance the mental efficiency of the older women. Interview schedule method was adopted to collect the required data from the respondents. This study was carried out at Asoor village of Perambalur district and purposive sampling method was used to collect the data from 55 respondents. The major findings of the study revealed that majority of the respondents (74.5%) have moderate level of depression and mental efficiency